Optimization of recirculating water scallop larval cultivation system based on EDEM-fluent coupling - Li, Xiuchen; Yang, Yu; Liu, Dongshuo; Chen, Shuo; Wu, Shuqiao; Yuan, Xiang; Liu, Zibo; Wang, Yubao; Zhang, Hanbing (Frontiers in Marine Science, 2024)
This article aims to address the issues of low cultivation density and high labor intensity of manual water exchange in existing scallop seedling ponds, an upwelling recirculating water system for scallop larval cultivation is designed. EDEM-Fluent coupled model was used to simulate the movement of scallop larvae in the culture cone in order to guarantee the uniform distribution of larvae in the cultivation device. Design-Expert software was utilized to investigate the impact of the bottom cone angle(θ), the column height/cone height ratio(n) and the inflow velocity(v) on the variation coefficients of the axial and radial distributions of D-shaped larvae within the culture cone. The results indicated that θ = 108.97° and n = 1.8 represent the ideal structural parameters for the culture cone. The further investigation of the culture cones prototype was conducted to examine the impact of the inlet deflector angle (α), cultivation density (τ), and inflow velocity (v) on its performance. θ=108.97°, n=1.8, v=0.19m/s, α=60.94°, and τ=110pcs/ml were found to be the ideal combination of parameters, in this scenario, the D-shaped larvae’s radial distributions’ coefficients of variation is 22.13%, the error between the experimental and simulation results is 4.41%. Research has shown that EDEM-Fluent based simulation analysis methods can be used for the design and parameter optimization of upwelling recirculating water scallop larval cultivation system, this paper can provide a reference for the design of an upwelling recirculating water scallop larval cultivation system.